2003
DOI: 10.1081/ncn-120025240
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and Inhibition by 2′-O-Hydroxyethyl Residues of Gene Targeting Mediated by Triple Helix Forming Oligonucleotides

Abstract: Reagents that recognize and bind specific genomic sequences in living mammalian cells would have great potential for genetic manipulation, including gene knockout, strain construction, and gene therapy. Triple helix forming oligonucleotides (TFOs) bind specific sequences via the major groove, but pyrimidine motif TFOs are limited by their poor activity under physiological conditions. Base and sugar analogues that overcome many of these limitations have been described. In particular, 2'-O-modifications influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Although our efforts to improve the biological activity of the TFOs were not successful, we think it likely that improvements are possible. However, on the basis of this and a previous study (42), we have concluded that additional sugar modification is unlikely to be effective. It should be noted that the contribution of the sugar analogues is inherently nonselective with respect to sequence.…”
Section: Discussionmentioning
confidence: 56%
“…Although our efforts to improve the biological activity of the TFOs were not successful, we think it likely that improvements are possible. However, on the basis of this and a previous study (42), we have concluded that additional sugar modification is unlikely to be effective. It should be noted that the contribution of the sugar analogues is inherently nonselective with respect to sequence.…”
Section: Discussionmentioning
confidence: 56%
“…Thec omplexes were characterised by 1 H, 13 Ar ange of ONs targeting as pecific location of GFP plasmid DNAw ere selected. These TFOs were designed to incorporate alkyne-modified bases for functionalisation through click chemistry with azide-modified cis-platinum(II) complexes.T he design of the TFOs included several considerations that have previously led to effective triplex formation, including:1 )TFOs were generated as homopyrimidine oligomers to afford effective Hoogsteen base recognition of the target duplex;2 )a low number of triplet inversions and mismatches were included to prevent destabilization;a nd 3) the number of consecutive C + -GC triplets was minimized to avoid electronic repulsion, which reduces their stabilising effects at low pH values.Pt II -TFOs hybrids were generated by clicking Pt-N 3 -Cis (5), Pt-N 3 -Carbo (7), or Pt-N 3 -Oxali (8)t o the alkyne-modified TFOs (Figure 3) as described in the Supporting Information (S-1.4). Al ibrary of five TFOs were developed that were between 21-29 nucleotides in length (Figure 3B).…”
Section: Methodsmentioning
confidence: 99%
“…[4] Recent work has,therefore,focused on enhancing target binding properties and maximising their lifetimes in cellular environments.A sp art of this effort, the introduction of acovalent crosslinking agent such as psoralen into TFO constructs has shown significant promise (Figure S-1). [5] Here,crosslinking is initiated by UV light [6] to produce gene-specific mutations [7] that inhibit transcriptional activity. [8] Alternatively,t he use of TFOs as targeting probes that discretely transport platinum(II) crosslinking agents to selected duplex targets has also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…As part of this effort, the introduction of a covalent crosslinking agent such as psoralen into TFO constructs has shown significant promise (Figure S‐1). [5] Here, crosslinking is initiated by UV light [6] to produce gene‐specific mutations [7] that inhibit transcriptional activity. [8] Alternatively, the use of TFOs as targeting probes that discretely transport platinum(II) crosslinking agents to selected duplex targets has also been explored.…”
Section: Introductionmentioning
confidence: 99%